Cultivation of immature Capsicum spp. embryos for incompatible-crossing embryo rescue (Acta Scientiarum. Agronomy, 2018)
The in vitro culture of embryos is an important technique to enable the rescue of embryos from incompatible crosses. Studies analyzing the factors that affect the in vitro culture of zygotic embryos are scarce. This study evaluated the effect of the genotype (Capsicum baccatum and C. frutescens), the composition of the culture medium (MS and ½ MS medium with different concentrations of sucrose, IAA and GA3) and the stage of development (globular, cordiform, torpedo and cotyledonary) in the in vitro culture of immature embryos. Embryo germination was influenced primarily by the stage of development of the embryo and the composition of the culture medium. Regardless of the species, the most suitable culture medium for the germination of globular and cordiform embryos was ½ MS with 0.05 mg L-1 of GA3 and IAA and 40 g L-1 of sucrose. For torpedo and cotyledonary embryos, ½ MS culture medium with 20 g L-1 of sucrose without phytoregulators is recommended for germination. These results were better than those described in the literature for all development stages in the two species. The results in the present study will be useful for geneticists and genetic enhancers interested in applying germination techniques conducted in vitro for immature Capsicum embryos.